Number of Urogenital Disorders Visits in The Emergency Room of dr. H. Andi Abdurrahman Noor General Hospital - Bayu Saputera; Heru Prasetya (Fakultas Kedokteran Universitas Lambung Mangkurat, 2020)
Abstract: In urology, urogenital disorders include all male and female urinary tract and male genital organ abnormalities. These disorders can be an infections, blockages due to foreign bodies, dysfunction due to pathological or degenerative processes, trauma, neoplasms, or congenital disorders. This research was a retrospective descriptive study to determine the number of patient visits with urogenital disorders. The place of this research was ER of DHAAN General Hospital, Tanah Bumbu District, South Kalimantan Province, Indonesia. The research data was taken from data on new patient visits to the ER in 2017. The number of patient visits with urinary tract disorders was 475 cases: male 57.1% and female 42.9%. The most cases based on the type of disorder was UTI (38.9%), second was urolithiasis (25.3%), and third was CKD (23.4%). While the number of patient visits with male genital disorders was 79 cases. Most cases was BPE (86.1%). Knowing the number of patient visits with urogenital disorders will make the clinicians be directed in preparing themselves for urogenital emergencies in their respective health services. Keywords: DHAAN, number of visits, urogenital disorders, urology.